Pengaruh Model Pembelajaran Realistic Mathematics Education (RME) Berbantuan Geogebra Terhadap Kemampuan Berpikir Kritis Siswa dan Hasil Belajar Kognitif Matematika Siswa Kelas V Sekolah Dasar - Agnes Fredi; Neza Agusdianita; Osa Juarsa (UNIB Press, 2026)
This study aims to determine the effect of the Realistic Mathematics Education (RME) model assisted by GeoGebra on students’ critical thinking skills and cognitive learning outcomes in mathematics, as well as to analyze the correlation between the two variables. This research employed a quasi-experimental design with a pretest–posttest control group design. The participants consisted of 44 fifth-grade elementary school students divided into an experimental class and a control class. The instruments used were an essay test for measuring critical thinking skills and a multiple-choice test for assessing cognitive learning outcomes. Data were analyzed using normality and homogeneity tests, N-Gain, independent sample t-test, and Pearson Product Moment correlation with the aid of IBM SPSS Statistics version 22. The results showed that the RME model assisted by GeoGebra had a significant effect on improving students’ critical thinking skills (t = -2.342; Sig. 0.027 < 0.05) with an N-Gain value of 0.65 (moderate–high category). The model also significantly influenced students’ cognitive learning outcomes in mathematics (t = -3.176; Sig. 0.004 < 0.05) with an N-Gain value of 0.67 (moderate–high category). Moreover, there was a strong positive correlation between critical thinking skills and cognitive learning outcomes (r = 0.742; Sig. 0.000 < 0.05). These findings indicate that the Realistic Mathematics Education (RME) model assisted by GeoGebra is effective in enhancing students’ critical thinking and cognitive performance while fostering a positive interrelationship between both aspects. Therefore, this model is recommended as an innovative learning approach to develop higher-order thinking skills in elementary mathematics education.